Full-term newborns’ readiness during the first breastfeeding in rooming-in - Calegari, Fernanda Luciana; Barbieratto, Bianca Jora; Fujinaga, Cristina Ide; Fonseca, Luciana Mara Monti; Oliveira, Caroline Ramos de; Leite, Adriana Moraes (Rev Rene, 2016)
Objective: to analyze the full-term newborn’s readiness to suck the mother’s breast in the first breastfeeding in rooming-in. Methods: analytical quantitative study  with 43 full-term newborns. Results: the states of sleep and wakefulness prevailing before breastfeeding were 41.9% alert and quiet during breastfeeding, 48.8% active sleep. In all domains assessed in the conduction of breastfeeding, the favorable signs had the highest percentage: Body posture (85.6%); Newborn responses (82.3%); Emotional bond (73.8%); Breast anatomy (100.0%); Suction by the newborn (86.1%); Time spent in the suction (78.4%). The average of the breastfeeding time was 12.08 minutes. Conclusion: full-term newborns showed good readiness to suck maternal breast in the first breastfeeding, since they prevailed in active state, showed good frequency of suction and in the conduction of breastfeeding, most of the signs were favorable to it.